A conversation with Joseph Lau. (8th April 2014) - Cappelleri, Joseph C.; Ingerick, Meghan
Abstract : Dr. Joseph Lau is a world‐leading expert in meta‐analysis and systematic reviews. Currently a professor in the Department of Health Services, Policy and Practice and co‐director of the Center for Evidence‐based Medicine at Brown University, Professor Lau has applied evidence‐based methods to a variety of clinical, biomedical and healthcare topics; has developed reliable and efficient methods and tools to conduct systematic reviews and meta‐analyses; and has advanced an understanding on the impact of factors that may contribute to differences of results in scientific studies. His past research includes cumulative meta‐analysis of randomized controlled trials, comparison of results from large trials and meta‐analyses of small trials, effect of baseline risk in the interpretation of clinical trial results, and empirical evaluation of existing methods of combining data. His current focus is on a Web‐based repository of systematic review data, reviews of diagnostic tests, nutrition, clinical practice guidelines, and dissemination of evidence‐based methods to varied health‐care disciplines. This report is a conversation from an adapted version of an interview, more or less chronologically arranged, between Joseph C. Cappelleri as interviewer and Joseph Lau as interviewee, with Meghan Ingerick recording and transcribing the interview. Copyright © 2014 John Wiley & Sons, Ltd.